Parece construção e já é ruína: para a crítica de uma utopia nacional-desenvolvimentista - Henrique Leão Coelho (2022)
The thesis in question carries out an ontological critique of the updated nationaldevelopmentalism vocalized and supported by the prominent and intellectualized politician and author Ciro Gomes. This being the central objective, it is presented as an adjacent objective the resumption of high points of the ideological set related to reactionary/conservative nationalism in Brazil, which will contribute, once the contours and circumscriptions of alien ideologies are carried out, with the excavation of the specificity of the ideology of C. Gomes. It is necessary to support that ontological criticism flees from assertions that give autarky or absolute autonomy to consciousness, thought, ideation, intellection. Ontological criticism means capturing the genesis, specificity and function of a social praxis or a teleology-ideology present in the plethora of social praxis that configure a sociability. Therefore, in order to achieve the aforementioned ontological critique, an apprehension of the particular effective reality of Brazilian capitalism becomes necessary, that is, the maximum concreteness or particularization of the Brazilian capitalism's mode of existence.